E-021 Effect of early sanguinate® infusion on cerebral blood flow to the ischemic core in experimental middle cerebral artery occlusion. (4th August 2020) - Christoforidis, G; Saadat, N; Niekrasz, M; Roth, S; Carroll, T
Abstract : Purpose: Sanguinate (Prolong Pharmaceuticals, South Plainfield, NJ) is an investigational bio-pharmaceutical blood substitute that facilitates the transfer of oxygen to oxygen-deprived cells and tissues using a bovine PEGylated carboxyhemoglobin-based oxygen carrier designed to release oxygen in hypoxic tissue. Through its vasodilatory effects at the pial arteriolar level, its ability to deliver oxygen to severely hypoxic tissues, oncotic effect and anti-inflammatory effects, Sanguinate shows promise in slowing the progression of ischemic insult in acute stroke. We hypothesize that Sanguinate improves cerebral blood flow to the ischemic core in the early stages of MCA occlusion (MCAO). Methods: Using an IACUC approved protocol, eight mongrel canines (20–30 kg) underwent angiographically-guided endovascular permanent MCA occlusion. Four subjects received Sanguinate (8 mL/kg) starting 30 minutes following MCA occlusion and four subjects received a similar volume of normal saline (controls). Physiologic parameters pH, PaO2, PaCO2, glucose, hematocrit, mean arterial blood pressure, ETCO2, temperature and glucose were monitored and kept within physiologic limits. Anesthetics were chosen to minimize cerebrovascular effects. Cerebral blood flow (CBF) was assessed using neutron-activated microspheres (Biopal, Inc, Worcester, MA, USA) at three time points: 1) prior to MCAO, 2) 30 minutes following MCAO and 3) 30 minutes following Sanguinate/saline infusion. Pial collateral recruitment was scored and measured by arterial arrival time 30 minutes post MCAO (immediately prior to Sanguinate/saline infusion) and 30 minutes post Sanguinate/saline infusion. Diffusion-weighted MRI (3T Achieva, Philips Healthcare, Best, Netherlands) was used to assess infarct volume 2 hours following MCAO. CBF values, infarct volumes and arterial arrival time in the control and treatment groups were compared using one-way analysis of variance assuming equal variances with significance defined at the 5% level. Results: Mean infarct volumes two hours following MCAO for control and Sanguinate treated subjects were 2122 mm 3 and 2440 mm 3 (p=0.8173), respectively. Relative to pre-treatment post-MCAO CBF, CBF measured 30 minutes following Sanguinate infusion increased by a mean of 25.2% whereas in controls CBF increased by a mean of 1.44% following saline infusion (p=0.0270; figure 1 ). Pre-treatment pial collateral recruitment between treatment and control groups were nearly identical. Arterial arrival time following treatment decreased by a mean of 0.49 seconds in the treatment group and increased by a mean of 0.12 seconds in the control group (p=0.0081). Conclusion: Preliminary results indicate that Sanguinate administered in the early acute phase of ischemic stroke improves CBF to the core infarct zone in experimental MCAO immediately following its administration. Disclosures: G. Christoforidis: 1; C; NIH grant. N. Saadat: None. M. Niekrasz: None. S. Roth: 1; C; NIH grant. T. Carroll: 1; C; NIH grant.